(untitled) (Journal of actual problems of jurisprudence, 2022)
The current international situation draws the attention of the whole society to the issues of population migration. The migration of millions of people causes concern both at the state and at the public level. Of great importance are theoretical scientific research that explains the content of these processes. A prerequisite for the development of a new concept of the migration policy of the Republic of Kazakhstan for 2022-2026 is the consideration of scientific foundations. Although there are studies on the topic of migration, there are not many works in the domestic literature regarding its typology and classification. If, when studying any topic, the conceptual apparatus and its classification are not determined, then there may be various misunderstandings, as a result of which erroneous decisions can be made. Therefore, the definition of the basic concepts, types, classifications of each phenomenon is of great importance. There are several options for the typology and classification of population migration among the scientific community. In this article, an analysis of fundamental and modern scientific opinions from near and far abroad on the topic is carried out, a typology of population migration is proposed. In addition, its difference from the classification of migration is indicated. This is a systematic work to make a reasonable contribution to a comprehensive understanding of the phenomenon of migration, its classification according to characteristics, the exchange of scientific opinions in the direction of the multiplicity of species. Keywords: population migration, typology of population migration, classification of population migration, signs of population migration.